The calculation of player speed from tracking data - Wu, L. Y.; Swartz, T. B. (International Journal of Sports Science & Coaching, 2023)
This short communication considers the calculation of player speed from tracking data. Whereas there are many player tracking systems, all rely on the collection of Cartesian coordinates corresponding to the players on the pitch. From these Cartesian coordinates, there are many ways that one could approximate player speed and acceleration. We introduce some simple principles from exploratory data analysis, which help yield more reliable speed calculations. The general principles are illustrated on various player tracking systems.